Cybersecurity in Engineering Management: A Review of Strategies to Protect Critical Infrastructure - Gharibi, Sajjad (Management Strategies and Engineering Sciences, 2022)
This article provides a comprehensive narrative review of cybersecurity strategies in the context of engineering management, with a particular focus on protecting critical infrastructure. As the digitization of critical infrastructure continues to accelerate, engineering managers are increasingly required to integrate cybersecurity considerations into their management practices. This review examines the historical context of cybersecurity in engineering management, the current trends in cyber threats, and the unique vulnerabilities of critical infrastructure. It also explores the role of engineering managers in implementing cybersecurity policies, fostering cross-disciplinary collaboration, and overcoming technical, organizational, and regulatory challenges. Additionally, the article identifies emerging technologies, such as AI and IoT, that are likely to influence the future of cybersecurity in engineering management and highlights key research gaps that need to be addressed. The findings underscore the importance of adopting a proactive and comprehensive approach to cybersecurity, emphasizing the need for continuous improvement and the alignment of security measures with organizational goals.